Cloacal microbiome variation in wild and captive Eastern Indigo Snakes (Drymarchon couperi) with and without Cryptosporidium serpentis infection - Christopher Roger Brown; Mark Nikolaus Yacoub; James E. Bogan; Matthew D. Buehler; Michelle Lea Hoffman; Janina Alessandra Krumbeck; Zachary J. Loughman (PLoS ONE, 2026)
The Eastern Indigo Snake (EIS; Drymarchon couperi ), a federally threatened species native to the southeastern United States, serves as a valuable model for examining the effects of captivity and infection on gastrointestinal microbial composition in reptiles. As an alternative to direct gut sampling, we examined the cloacal microbiomes of EISs to evaluate changes in microbial community structure across our study groups. This study assessed the cloacal microbiome of wild and captive EISs using shotgun metagenomic sequencing. Samples were divided into three groups for comparative microbiome analysis: captive snakes positive for Cryptosporidium serpentis ( C. serpentis ), captive snakes negative for C. serpentis , and wild snakes. Alpha (Shannon index, paired Wilcoxon test) and beta diversity (Bray-Curtis dissimilarity, PERMANOVA, CAP) metrics were used to assess microbial diversity and community composition across groups. Furthermore, a linear discriminant analysis effect size (LEfSe) was used to identify microbial taxa significantly enriched in C. serpentis -positive versus C. serpentis -negative captive snakes. Bacterial, fungal, bacteriophage, nematode, and protozoan taxa were significantly enriched in C. serpentis -positive snakes compared with C. serpentis -negative captive snakes, based on a linear discriminant analysis (LDA) score ≥ 2.5 and p ≤ 0.05. Total taxa species Shannon diversity was consistent between C. serpentis -positive and negative captive snakes (p = 0.55) while wild snake samples were significantly more diverse (p = 0.026). Wild snakes also exhibited a significantly increased Shannon diversity of fungi (p = 0.044), protozoa (p = 0.012), and nematodes (p = 0.008) compared to their captive counterparts. This study offers the first in-depth characterization of the cloacal microbiome in reptiles, specifically in EISs, using shotgun metagenomic sequencing. The findings establish a foundation for exploring microbiota–host interactions with implications for reptile health, disease ecology, and conservation management.